Solicitation of nanoparticles/fluids in solar thermal energy harvesting: A review. (2020) - Mausam, Kuwar; Kumar, Sumit; Kumar Ghosh, Subrata; Kumar Tiwari, Arun; Sehgal, Mudit
Abstract: One of the most alternative for conventional fossil fuels, with any harmful effect like emission of greenhouse gases, global warming etc. is solar power energy system (SPESs). Solar power energy system has capability to convert solar energy in to heat energy and top most useable energy mode electricity. Due to presence of good thermo physical properties of different nanoparticles and nanofluids are better option to enhancing the performance of SPESs on thermal ground. This review article deals with the study of latest development in field of solar energy power system like different solar collectors, solar based water heater, solar based geothermal power system, solar water desalination, solar photovoltaic and solar thermal system based of nanoparticle and nanofluids.